The Influence of Service Excellence, Customer Experience, and Social Media Marketing on Purchase Decisions: A Case Study at CV Bali Stars Promosindo, Ubud Branch - I Gusti Ayu Vira Rahmawati; Ni Nyoman Sudiyani; I Made Sumartana (Countable (Contemporary Business and Sustainability Science), 2025)
This study aims to examine the influence of service excellence, customer experience, and social media marketing on purchasing decisions. This study was conducted at CV Bali Stars Promosindo Ubud Branch. The design used is quantitative research that is descriptive and causal associative. The population used is all customers who have made transactions at CV Bali Stars Promosindo Ubud Branch. The sampling technique used non-random sampling with a purposive sampling method, so that 96 people were used. This study uses quantitative data types with primary and secondary data sources.Data collection methods use observation, interviews, documentation studies and questionnaires. Data processing uses the SPSS program version 25 for Windows. Data analysis uses instrument tests, classical assumption tests, multiple linear regression analysis, determination analysis, F-tests and t-tests. The results of the study indicate that (1) Service excellence, customer experience, and social media marketing simultaneously have a positive and significant effect on purchasing decisions, (2) Service excellence has a positive and significant effect partially on purchasing decisions, (3) Customer experience has a positive and significant effect partially on purchasing decisions and (4) Social media marketing has a positive and significant effect partially on purchasing decisions.